Evaluasi pelatihan desain kreatif transformasi tanah liat dan pipa PVC menjadi karya seni untuk anak berkesulitan belajar - Julius Nugroho; Jihan Nabila Meilieani; Jihan Fadhila Meilieana; Vincent Cornelius Rinaldy; Theofan Cristopher Gurning; Syahwa Aliah Wandi (Penamas: Journal of Community Service, 2026)
Children with learning difficulties have learning characteristics that differ from those of children in general, requiring adaptive, inclusive, and experience-based learning approaches. This Community Service Program aimed to develop children’s non-cognitive skills through a sculptural craft art workshop using recycled PVC pipes and clay as learning media. The program was conducted in collaboration between Universitas Tarumanagara and Yayasan Peduli Anak Spesial on November 5, 2025, and involved lecturers and undergraduate students. A qualitative approach was employed using observation, interviews, and hands-on practice. The training was designed gradually, beginning with visual demonstrations and progressing to intensive assistance during the creation of sculptural craft artworks in the form of pencil holders. Visual and tactile approaches were selected because they align with children’s learning patterns, which respond better to concrete media and motor-based activities. The results indicate improvements in fine motor skills, creativity, and focus. Despite initial limitations in preparation, the program demonstrates that sculptural craft art can serve as an effective and inclusive learning alternative in formal and non-formal education settings.